2018
DOI: 10.1002/minf.201800078
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Modeling, Ranking and Prioritization of Pharmaceuticals Using QSTR and i‐QSTTR Approaches: Application of 2D and Fragment Based Descriptors

Abstract: This paper is dedicated to Prof. Paola Gramatica on the occasion of her retirement.Abstract: There is a huge lack of experimental data on ecotoxicity of pharmaceuticals, while existing resources are insufficient to gather these data against all possible environmental endpoints. Computational tools such as quantitative structure-toxicity relationship (QSTR) can help us to a great extent to overcome this problem through filling of data gaps. In the current study, QSTR models have been developed for toxicity of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The higher toxicity values have often been associated with increased lipohilicity. ,, The most toxic compounds were hydrophobic and acted as hydrogen-bonding or electron acceptors (e.g., hydrophobic nitroaromatic compounds with halogen and amino substituents ,,,, ). Khan et al (2019) have advised that if a hydrophobic group is necessary during the design of a drug compound, a higher polarity substitution should be preferred. Voutchkova et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher toxicity values have often been associated with increased lipohilicity. ,, The most toxic compounds were hydrophobic and acted as hydrogen-bonding or electron acceptors (e.g., hydrophobic nitroaromatic compounds with halogen and amino substituents ,,,, ). Khan et al (2019) have advised that if a hydrophobic group is necessary during the design of a drug compound, a higher polarity substitution should be preferred. Voutchkova et al.…”
Section: Resultsmentioning
confidence: 99%
“…50,88,89 The most toxic compounds were hydrophobic and acted as hydrogen-bonding or electron acceptors (e.g., hydrophobic nitroaromatic compounds with halogen and amino substituents 52,53,81,90,91 ). 92 have advised that if a hydrophobic group is necessary during the design of a drug compound, a higher polarity substitution should be preferred. Voutchkova et al ( 2011) 93 have suggested keeping logPo/w < 2 and ΔE (LUMO−HOMO) > 9 eV to increase the likelihood of designing a compound with low aquatic toxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Given the expense and other resources required to conduct toxicity tests, ecotoxicity/toxicity data for PPCPs are limited in terms of both the number of PPCPs tested and the types of apical effects examined. Therefore, researchers predict the potential hazards of PPCPs via in silico quantitative structural–activity relationship (QSAR) modeling, which is used, for example, in the USEPA's PBT Profiler, CTV Predictor, and EPISuite software including BIOWIN, BCFBAF, and ECOSAR (Diamond et al, 2011; Golbaz et al, 2021; Kar et al, 2018; Khan, Benfenati, et al, 2019; Khan, Kar, et al, 2019). In particular, the current hazard‐based prioritization studies rely heavily on predicted PBT data using various QSAR models, which remain to be experimentally validated (Guo et al, 2016).…”
Section: What Is Our Understanding Of Ppcps and Approaches For Priori...mentioning
confidence: 99%
“…Since 2006, the European regulation on the Registration, Evaluation, Authorization and Restriction of Chemicals (REACH) [2] requires a mandatory preliminary assessment of their toxicity to aquatic organisms before starting production and trade. To address this challenge, many QSAR studies have been conducted and reported for different aquatic toxicity endpoints [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%